KMnO4-mediated reactions for hexachlorophene in aqueous solutions: Direct oxidation, self-coupling, and cross-coupling. (November 2020) - Cao, Wanming; Yu, Yao; Wei, Junyan; Al-Basher, Ghada; Pan, Xiaoxue; Li, Beibei; Xu, Xinxin; Alsultan, Nouf; Chen, Jing; Qu, Ruijuan; Wang, Zunyao
Abstract: Hexachlorophene (HCP) is used in a range of general cleaning and disinfecting products and has received increased attention due to its damaging effect to the central nervous system in animals and its toxicity in humans. The chemical oxidation of HCP by KMnO4 was performed to systematically evaluate the effects of oxidant dose, pH, temperature, typical anions, humic acid (HA), and various matrices on HCP removal. The second-order rate constant for HCP was determined to be 4.83 × 10 4 M −1 s −1 at pH 7.0 and 25 °C. The presence of HA can inhibit the removal of HCP by KMnO4, while Cl −, NO3 −, SO4 2−, PO4 3−, and CO3 2− have negligible effects. Degradation products analysis of the reaction, as well as theoretical calculations of HCP molecule and its phenoxy radical species, indicated that KMnO4 oxidation for HCP included a C–C bridge bond cleavage, hydroxylation, direct oxidation and self-coupling, and cross-coupling reactions. This study revealed that KMnO4 oxidation is an effective technique for eliminating HCP in real water and wastewater. Graphical abstract: Image 1 Highlights: The degradation processes of HCP by KMnO4 were systematically studied. Seventeen intermediates of HCP were detected by LC-Q-TOF-MS. The oxidation of HCP mainly involves C–C bridge bond cleavage, hydroxylation, direct oxidation and coupling reactions. Density functional theory was employed to determine the reaction sites of HCP.